Overcoming The Anxiety In Speaking English - Siregar, Nuri Handayani; Santoso, Didik (Yayasan Daarul Huda Kruengmane, 2024)
This research article discusses strategies for overcoming anxiety in speaking English as developed by Kondo and Ying-Ling (2004), those are; Preparation, Positive Thinking, Relaxation, Peer Seeking and Resignation. The study aims to address the anxiety frequently experienced by students as foreign language speakers when speaking English. This learning strategy model is expected to alleviate these issues so that students no longer feel anxiety when speaking English as a second language.